2006
DOI: 10.1016/j.molcel.2006.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Histidine Phosphorylation of the Potassium Channel KCa3.1 by Nucleoside Diphosphate Kinase B Is Required for Activation of KCa3.1 and CD4 T Cells

Abstract: The Ca2+ -activated K+ channel KCa3.1 is required for Ca2+ influx and the subsequent activation of B and T cells. Inhibitors of KCa3.1 are in development to treat autoimmune diseases and transplant rejection, underscoring the importance in understanding how these channels are regulated. We show that nucleoside diphosphate kinase B (NDPK-B), a mammalian histidine kinase, functions downstream of PI(3)P to activate KCa3.1. NDPK-B directly binds and activates KCa3.1 by phosphorylating histidine 358 in the carboxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
173
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(182 citation statements)
references
References 32 publications
(74 reference statements)
6
173
0
2
Order By: Relevance
“…28 In addition to the upregulation of K Ca 3.1 current and K Ca 3.1 expression by AGEs, the recent studies reported that K Ca 3.1 channels were activated by PI(3)P, which is produced by PI3K from phosphatidylinositol. [29][30][31] Decreasing intracellular level of PI(3)P can reduce K Ca 3.1 channel activity. 32 Besides, recombinant human K Ca 3.1 channels induce HEK293 cell proliferation by a direct interaction with ERK1/2 pathways 33 and downregulating ERK reduces K Ca 3.1 channel expression.…”
Section: Discussionmentioning
confidence: 99%
“…28 In addition to the upregulation of K Ca 3.1 current and K Ca 3.1 expression by AGEs, the recent studies reported that K Ca 3.1 channels were activated by PI(3)P, which is produced by PI3K from phosphatidylinositol. [29][30][31] Decreasing intracellular level of PI(3)P can reduce K Ca 3.1 channel activity. 32 Besides, recombinant human K Ca 3.1 channels induce HEK293 cell proliferation by a direct interaction with ERK1/2 pathways 33 and downregulating ERK reduces K Ca 3.1 channel expression.…”
Section: Discussionmentioning
confidence: 99%
“…Two isoforms of nucleoside diphosphate kinase (NDPK): Nme1/NDPK-A [9][10][11][12][13] and Nme2/NDPK-B [14][15][16][17][18][19] have been characterized as mammalian His kinases. Other mammalian His kinases exist.…”
mentioning
confidence: 99%
“…8 For K Ca 3.1 the nucleoside diphosphate kinase B phosphorylates histidine 358 in the C-terminal, which is permissive for Ca 2C activation. 18 K Ca 2 channels expressed in the soma of neurons are functionally coupled to voltage-activated Ca 2C channels (Ca v channels) and give rise to Ca 2C -dependent afterhyperpolarizations of medium duration (mAHP) following single or trains of action potentials, which is an essential component of early spike frequency modulation in cortical and limbic neurons. 19 In pacemaker neurons of the basal ganglia and cerebellum, cyclic activation of K Ca 2 channels secures highly regular firing, which is essential for muscle coordination and movement.…”
Section: Pharmacological Modulation Of Ion Channel Gatingmentioning
confidence: 99%